Community Preparedness in Facing Flood Disaster in Martapura Timur District, Banjar Regency - Saifullah Saifullah; Deasy Arisanty; Parida Angriani; Nefy Farista; Akhmad Munaya Rahman (Universitas Lambung Mangkurat, 2023)
This study is to examine community preparedness as an effort to mitigate flood disasters. Research related to community preparedness in dealing with disasters is needed to manage disasters in the future. Thus, this is the first step in building a disaster-aware community. So that when a disaster occurs, the community has the attitude and ability to understand how to prepare for a flood disaster. This type of research is quantitative, with data analysis used with quantitative descriptive methods. Data collection is used by directly collecting the results of questionnaires prepared in advance to the public and collecting documents related to research variables using survey methods. The research was conducted in Martapura Timur District, Banjar Regency. This study analyzes the community s preparedness data in dealing with floods by using data analysis of the percentage of community preparedness to face flood disasters. Community preparedness is calculated based on an interval classification of community preparedness scores based on five parameters: knowledge and attitudes, policies and guidelines, emergency response plans, disaster warning systems, and the ability to mobilize resources. The results of the scoring analysis regarding community preparedness in dealing with flood disasters in Martapura Timur district show that the highest answer score is mainly between the 8-15 interval with a frequency of 192 research respondents with a percentage of 56% of the total 344 research respondents. These results show that community preparedness in facing flood disasters is low.